ITLN1 inhibits tumor neovascularization and myeloid derived suppressor cells accumulation in colorectal carcinoma - Chen, Li; Jin, Xiao-Han; Luo, Jie; Duan, Jin-Ling; Cai, Mu-Yan; Chen, Jie-Wei; Feng, Zi-Hao; Guo, Austin Meng; Wang, Feng-Wei; Xie, Dan (Oncogene, 2021)
Low levels of ITLN1 have been correlated with obesity-related colorectal carcinogenesis, however, the specific functions and underlying mechanisms remain unclear. Thus, we sought to explore the inhibitory role of ITLN1 in the tumor-permissive microenvironment that exists during the first occurrence and subsequent development of colorectal carcinoma (CRC). Results indicated that ITLN1 was frequently lost in CRC tissues and ITLN1 to be an independent prognostic predictor of CRC. Orthotopic and subcutaneous tumor xenograft approaches were then used to further confirm the protective role of ITLN1 during tumor progression. Increased ITLN1 expression in CRC cells significantly inhibited local pre-existing vessels sprouting, EPC recruitment and the infiltration of immunosuppressive myeloid-derived suppressor cells (MDSCs) into tumor tissues without affecting the behavior of CRC cells in vitro. Comparatively, ITLN1-derived MDSCs had a lower suppressive effect on T cell proliferation, NOS2 expression, and ROS production. In addition, ITLN1 overexpression markedly suppressed bone marrow (BM)-derived hematopoietic progenitor cells (HPC) differentiation into MDSCs as well as NOS2 activity on MDSCs. Using H-2b+YFP + chimerism through bone marrow transplantation, increased ITLN1 in HCT116 significantly reduced the BM-derived EPCs and MDSCs in vivo mobilization. Mechanistically, results indicated ITLN1 inhibited tumor-derived IL-17D and CXCL2 (MIP2) through the KEAP1/Nrf2/ROS/IL-17D and p65 NF-ĸB/CXCL2 signaling cascades dependent on PI3K/AKT/GSK3ß. This effect was reversed by the PI3K selective inhibitor LY294002. Collectively, ITLN1 synergistically suppressed IL-17D and CXCL2-mediated tumor vascularization, bone marrow derived EPC recruitment, as well as MDSCs generation and trafficking. Thus, ITLN1 potentially serves as a critical prognostic and therapeutic target for CRC.